2019
DOI: 10.1186/s12917-019-1786-z
|View full text |Cite
|
Sign up to set email alerts
|

The organophosphate pesticide -OP- malathion inducing thyroidal disruptions and failures in the metamorphosis of the Senegalese sole, Solea senegalensis

Abstract: BackgroundOrganophosphate pesticides-OP-, like malathion, can alter the normal functioning of neuro-endocrine systems (e.g., hypothalamus-pituitary-thyroid-HPT- axis), and to interfere on the thyroidal homeostasis. Through direct interactions with thyroid receptors, an/or indirectly via up-stream signalling pathways, from the HPT axis (i.e., negative feedback regulation), malathion possess the ability to affect integrity of thyroidal follicular tissue, and it can also block or delay its hormonal functioning. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 107 publications
(164 reference statements)
0
18
0
Order By: Relevance
“…In goldfish, monocrotophos decrease TH levels, and up-regulate pituitary TSHβ and hepatic DIO1 and DIO3 expressions ( 397 ). In Senegalese sole, exposure to malathion affects growth patterns (eye migration, skeletal disorders), reduces thyroid follicle size, and induces decreased thyroid signaling (as seen by low TRβ mRNA levels) ( 398 ).…”
Section: Relevance Of the Thyroid Axis In Aquaculturementioning
confidence: 99%
“…In goldfish, monocrotophos decrease TH levels, and up-regulate pituitary TSHβ and hepatic DIO1 and DIO3 expressions ( 397 ). In Senegalese sole, exposure to malathion affects growth patterns (eye migration, skeletal disorders), reduces thyroid follicle size, and induces decreased thyroid signaling (as seen by low TRβ mRNA levels) ( 398 ).…”
Section: Relevance Of the Thyroid Axis In Aquaculturementioning
confidence: 99%
“…These alterations of physiology might impact survival rates leading to restocking failures through dwindling numbers of juveniles released into river estuaries (123). Ortiz-Delgado et al (124) investigated malathion exposure effects in the Senegalese sole, Solea senegalensis, a flatfish whose morphology, obtained gradually through metamorphosis, is THdependent. By exposing fish to malathion (another OPP), the authors demonstrated the sensitivity of this process to this pesticide that is still widely used in developing countries.…”
Section: In Vivo Evidence Of Thyroid Disruption From Animal Studiesmentioning
confidence: 99%
“…Numerous anthropogenic substances originating from industrial, pharmaceutical, and agricultural activities (herbicides, fungicides, and insecticides etc) are found in the environment. These substances majorly end up in the aquatic ecosystem, which becomes the warehouse of their residues (Ortiz-Delgado et al, 2019). Many of these substances have the potential to modulate the thyroid functions through different pathways including hormone synthesis and release, hormone transportation through the blood, hormone metabolism as well as the final clearance (Diamanti-Kandarakis et al, 2009).…”
Section: Chemical Factors In Amphibian Declinesmentioning
confidence: 99%